PENGARUH MANFAAT, KEMUDAHAN, KEAMANAN, SERTA FITUR LAYANAN TERHADAP MINAT MAHASISWA DALAM PENGGUNAAN DANA SEBAGAI E-WALLET - Panggabean, Embun Febryanti; Nasution, Muhammad Irwan Padli; Sundari, Sri Suci Ayu (Jurnal Ilmiah Sistem Informasi, 2023)
The purpose of this study is to confirm the usage of electronic wallets (also known as "ewallets") offered by the DANA application for making payments online. Electronic wallets have thus far been perceived as a technology that makes transactions simple and comfortable. Many individuals recognize the hazards associated with modern technology, particularly when it comes to payments. Despite being viewed as unsafe by some, many consumers still believe in it and utilize it. Therefore, in order to create a thorough technological acceptance model, this study takes into account risk and dependability variables. Risk and trust have an impact on how accepted electronic payment methods are, according to empirical research